In-situ observation of damage in unidirectional CMC laminates under tension. Issue 9 (15th June 2020) - Hilmas, A.M.; Henson, G.; Singhal, A.; Gao, Y.; Schuster, M.
Abstract: We observe microscopic damage progression in un-notched unidirectional SiC–SiC ceramic matrix composite laminates loaded monotonically in tension. In situ tensile testing was conducted in air at room temperature and combined with X-ray tomography imaging. The unidirectional specimens tested were novel double-reduced dogbones designed to develop matrix cracks in the synchrotron field of view. Multiple matrix cracks that rapidly traversed the section of each specimen were observed through the volume until the specimens broke into two pieces. The details of each matrix crack were tracked at each stress increment to better understand how the cracks evolve under load. One of the unidirectional specimens contains a matrix crack that displays a sharp 90° turn along the fiber direction in its final crack path. Fiber breaks were observed and several fibers in the unidirectional specimen showed multiple breaks. Fiber break opening was measured for each fiber break and the average fiber break opening for each stress increment is reported. The location and pullout distance of fiber breaks surrounding a matrix crack, as well as matrix crack spacing, are of modeling interest and are reported.